Educational Leaders’ Need for Health Literacy During the COVID-19 Pandemic (Journal of School Administration Research and Development, 2020)
School leaders will face great challenges balancing the health considerations of students and school staff with powerful political forces demanding that schools reopen as early as possible. In order to navigate this new educational landscape, school leaders will need to work with medical and public health officials to acquire health literacy. This will enable them to understand medically accurate information while rejecting politically inspired misinformation they will receive in the coming year. Health literacy will be an important skill needed by educational leaders to make the best possible decisions during this unprecedented pandemic.